FENOMENA DAKWAH BI AL-HIKMAH (Studi Kasus Jamaah Tharekat Syathariyah Di Madiun Selatan) - Daroini, Muchlis (Dialogia: Jurnal Studi Islam dan Sosial, 2018)
Abstract: The teachings of the Syathariyah in the South Madiun create a tradition of acculturation of traditions held by indigenous people and muslims. It also have a psychological impact on its supporters. The uniqueness of da'wah through tharekat (bathini), namely with bi al-h{ikmah produces an acculturative impact rather than provocative one. Even, at certain time, a tharekat teacher has become a role model, supervisor and problem solver for several life problems in the community. Tharekat Syathariyah is a Sufism philosophy which emphasized on the spiritual values in its teaching. The opposing between tharekat and local values makes this teaching has a distinctive follower which is from the lower class of society who believe in the noble values of previous ancestors. Therefore, the presence of this teaching shifted several traditions of society into Islamic traditions. This interaction is referred to as an acculturation of culture and it is considered as the characteristics of Islamic tasawwuf in Indonesia..ملخص: تعاليم الطريقة الشطارية في جنوب ماديون (Madiun Selatan) بالإضافة إلى خلق تقليد التثاقف من التعاليم التي لا تزال تحتفظ بها الشعوب الأصلية والإسلام، كما أن لها تأثير نفسي على ال‍سالك‍ين. إن خصوصية الدعوة من خلال أسلوب الطريقة (باطني) التي هي بالحكمة، تنتج نزعة ثقافية بدلاً من تصادمية. حتى في فترة من الوقت، أصبح مرشد الطريقة الثائر نموذجًا، معالجًا ومنورا في العديد من مشاكل الحياة للمجتمع. الطريقة الشطارية هي حركة التصوف تؤكد منذ زمن طويل قيم باطني في تعاليمها ، مثل معظم التعاليم الطريقة. إن مجرد اتصال بالقيم المحلية يجعل من هذه الطريقة قاعدة مميزة من المتابعين، أي الطبقة الدنيا من الناس الذين احتفظوا بالقيم النبيلة لأسلافهم السابقين. بحيث أن حضور الطريقة الشطارية ينقل بعض تقاليد المجتمع إلى تقاليد جديرة بقيمة الإسلام. ويُشار إلى هذا التفاعل بالترابط الثقافي الذي يميز التصوف الإسلامي في إندونيسيا.Abstrak: Ajaran-ajaran tharekat Syathariyah di Madiun Selatan selain mencipta tradisi akulturasi ajaran yang masih dipegang pribumi dan Islam juga memberikan dampak psikologis bagi pengamal-pengamalnya. Kekhasan dakwah melalui jalan tharekat (bathini) yaitu dengan bi l hikmah, menghasilkan dampak yang cenderung akulturatif daripada konfrontatif. Bahkan di beberapa waktu seorang guru tharekat menjadi panutan, juru sembuh dan pencerah dalam beberapa permasalahan kehidupan bagi masayarakat. Tharekat Syathariyah adalah gerakan tasawuf yang sejak lama menekankan kepada nilai-nilai bathini dalam pengajaranya, sebagaimana ajaran tharekat kebanyakan. Hanya saja persinggungan tharekat dengan nilai-nilai lokal menjadikan Tharekat ini mempunyai basis pengikut yang khas yakni masyarakat kelas bawah yang telah memegang nilai-nilai luhur nenek  moyang sebelumnya. Sehingga kehadiran Tharekat Syathariyah menggeser beberapa tradisi masyarakat menjadi tradisi yang cenderung  bernilai Islam. Interaksi inilah yang disebut sebagai sebuah akulturasi budaya yang menjadi ciri khas Islam tasawwuf di Indonesia.